Memory transfer as a medium to access intergenerational trauma across three generations in On Earth We’re Briefly Gorgeous by Ocean Vuong - Annisa Tusa'diyah Chaniago; Sri Sumaryani (Universitas Negeri Semarang, 2025)
The novel depicts the effect of the Vietnam War on the three generations, both during and long after the war. This article aims to show the portrayal of intergenerational trauma by three generations in On Earth We’re Briefly Gorgeous by Ocean Vuong. Through this analysis, each traumatic memory that is passed down from generation to generation will be explored. This analysis uses a qualitative descriptive method with the post-memory theory proposed by Marianne Hirsch. In consideration of that, the researcher will find the portrayal of intergenerational trauma experienced by the three generations in the novel, which are interconnected with each other. The results of this analysis indicate that the first generation, Lan, has schizophrenia and PTSD; the second generation, Rose, also has PTSD and anger issues due to their miserable life during the war; the third generation, Little Dog, who did not experience the Vietnam War at all was also affected through the transfer of memories such as stories, dark jokes, and verbally and physically abusive behavior. Therefore, through a collection of letters written by Little Dog, he tells the dark story of his family and his struggle in facing all the memories given.